Applying the FACTS? Framework: A Dual Example Case Study - Zak, Elizabeth (SXC Journal, 2026)
Visual misinformation is present in many formats, including graphs, user-generated images, and photographs. Although information literacy methods such as the CRAAP method or the RADAR framework are widely used to prevent the spread of verbal misinformation, new visual literacy methods are still relatively underexplored. The FACTS? method is applied to a comparative analysis of two graphs. Using a qualitative visual analysis, this study evaluates graph format, axis construction, color choice, title framing and source presentation. The findings suggest that the FACTS? method can be applied when comparing visual elements associated with information and misinformation. The use of two comparative graph cases enables deep, qualitative analysis of visualization strategies in a targeted case study. The findings of this paper highlight the need for further development in visual literacy education and continued exploration of the FACTS? method.